Assessing trust and research attitudes in Blacks/African Americans following a personalized vs less personalized community approach. (20th December 2022) - Bouges, Shenikqua; Noell, Debra; Osman, Fauzia; Benton, Susan Flowers; Clipps, Antwon D; Fischer, Barbara L.; Gooding, Diane C.; Anthony, Ruben L; Carter, Fabu P; Salazar, Hector; Simó, Carola A. Ferrer; Ennis, Gilda E.; et al.
Abstract: Background: Several studies have shown the importance of establishing trust in supporting an individual's willingness to participate in research; yet evidence is limited regarding systematic studies testing the effectiveness of various methods used to build trust. Our pilot study examined two methods of building trust in communities of color by measuring willingness to participate in research pre‐ and post‐intervention. We hypothesized that a more personalized intervention would be more effective than a non‐personalized one in changing attitudes about research participation. Methods: 97 non‐randomized African American participants, without self‐reported cognitive impairment, completed the research attitudes questionnaire (RAQ) before and after participating in two different community engagement (CE) activities: 1) personalized medication review (MR), n = 48; and/or 2) a less personalized public community talk (Talk), n = 49. Numeric comparisons were conducted using student t‐tests. We used chi‐square and Fisher's exact test for categorical comparisons. Pre‐ and post‐Talk and MR outcomes were tested for significant changes using the paired Wilcoxon non‐parametric sign rank test. Results: In this predominantly female sample (80% female), mean age was 64 (standard deviation = 9.9). Study participant characteristics provided in Table 1 . There were no significant differences in RAQ or trust questions in the pre‐ and post‐Talk session. However, during the MR session, significant changes were seen on the question "I have a positive view about medical research in general" (P = 0.007). During the pre‐MR, 16.7% strongly agreed with this statement, while 39.6% strongly agreed at the post‐MR. Similarly, agreement with the statements "Medical researchers treat people from my racial group as guinea pigs" (p = 0.004) and "Medical researchers work hard to keep participants' information private and secure" (P = 0.01) were also significantly different following the intervention (see Figure 5 ). Conclusions: These findings support our hypothesis that a more personalized community engagement approach would have a greater influence on participant's research attitudes. Compared to individuals with ≤ 1 co‐morbidities at baseline, those with ≥2 co‐morbidities had positive responses prior to an intervention and felt less responsibility to volunteer post med review. Additional studies are needed to further investigate these findings and the role of trust in association with research attitudes.